Royal Undergarment Corporation of the Philippines - Dy Juanco, Alejandro C. Jr.; Jose, Llanie E.; Ramos, Virgilio C.; Rosal, Samuel C.; Santos, Enrico; Tan, Remedios C. (Diliman, Quezon City College of Engineering, 1984)
Industrial Engineering 51 is a course on production system analysis. This project study not only applies the methods learned in this course, but also incorporates what we have learned fro other I.E. subjects like Engineering Economy and Systems and Procedures. This study includes a demand forecast which we recommended to be used to plan and program the future production activities of the enterprise. It also presents an improvement in supply management and quality control. Here, we compared the value of savings which can be gained in a sampling plan to the risk of having to accept complaints from an ordering or client company. Our documentation could also help the management of the company under study of their present system, aside from the recommendations we have made. This project was done with the idea that what has been done could be done better. It is the aim of the group to help the production system under study operate with greater effectiveness and economy.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems.
Feasibility study
Keywords: Royal Undergarment Corporation of the Philippines; Clothing trade; Production engineering